BREASTFEEDING AND BABY FIELD MASSAGE LOWER TOTAL BILIRUBIN IN NEWBORNS - Yunita Lukita Sari; Edy Soesanto; Yulisetyaningrum Yulisetyaningrum ((IJP) Indonesia Jurnal Perawat, 2025)
Neonates are newborns aged 0-28 days. One of the causes of neonatal death is caused by jaundice. The therapy applied is breastfeeding. One of the non-pharmacological approaches is baby field massage. This study aims to determine the effect of breastfeeding and baby field massage on the decrease in newborns' total bilirubin. Quantitative research with quasi-experimental design and one group pre and post-test design. The location of this research was carried out in the Perinatology Room from October to December. Infant bilirubin data is collected using secondary data, namely medical records. With breastfeeding and baby field interventions. Data analysis aims to describe the data being studied. With the Wilcoxone test type. Using a purposive sampling technique with a sample of 31 respondents with inclusion criteria: Babies born at full term on the 3rd to 28th day, jaundiced babies receive phototherapy, babies are given breast milk, Babies are given infant massage techniques. Exclusion criteria: Babies born under the moon, Babies born prematurely, Low birth weight, Very low birth weight of extra babies. The difference in total bilirubin levels before and after the intervention decreased with a significance value of p-0.000 less than 0.05. There is a significant difference in breastfeeding and baby field massage to lower total bilirubin in newborns Always support optimal breastfeeding for newborns and correctly learn baby field massage techniques.